2017
DOI: 10.21873/anticanres.11441
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dense Paclitaxel- and Carboplatin-based Neoadjuvant Chemotherapy Followed by Surgery or Concurrent Chemoradiotherapy in Cervical Cancer: a Preliminary Analysis

Abstract: Dose-dense NACT seems to achieve promising RRs with manageable toxicity in cervical cancer. Investigation on larger series with longer follow-up is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In our early experience, dose-dense chemotherapy obtained an overall response and optimal pathological response in 14 (82.3%) and in 3 (17.6%) of 17 patients, respectively (69). Histologically positive nodes, positive parametria and positive surgical margins were found in 12.5%, 18.7% and 6.2%, respectively, of the 16 patients who underwent radical hysterectomy.…”
Section: Neoadjuvant Chemotherapy Followed By Radical Surgerymentioning
confidence: 82%
“…In our early experience, dose-dense chemotherapy obtained an overall response and optimal pathological response in 14 (82.3%) and in 3 (17.6%) of 17 patients, respectively (69). Histologically positive nodes, positive parametria and positive surgical margins were found in 12.5%, 18.7% and 6.2%, respectively, of the 16 patients who underwent radical hysterectomy.…”
Section: Neoadjuvant Chemotherapy Followed By Radical Surgerymentioning
confidence: 82%
“…Surgery combined with preoperative neoadjuvant chemotherapy (intravenous or arterial infusion chemotherapy) is clinically employed to reduce tumor lesions and control subclinical metastases [ 12 , 13 ], and the commonly used chemotherapeutic agents include cisplatin, carboplatin, paclitaxel, bleomycin, ifosfamide, and fluorouracil [ 13 ]. Traditional open radical hysterectomy for cervical cancer includes extensive hysterectomy, bilateral adnexal resection, and pelvic lymph node dissection [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The response rates after NACT (79.2%) and after CCRT (90.0%) in our trial were similar to those reported in other studies [ 9 , 10 ]. The three-year PFS and OS might be higher than those reported in other studies (studies using dose-dense NACT followed by the CCRT strategy are listed in Table 4 [ 8 – 10 , 30 , 31 ]).…”
Section: Discussionmentioning
confidence: 61%